Qualidade fisiológica de sementes e crescimento inicial de mudas de Tabernaemontana fuchsiaefolia A. DC. - Moraes, Carlos Eduardo (2014)
Tabernaemontana fuchsiaefolia A. DC. (Apocynaceae), native from Brazil, with use in restoration of degraded areas due to high spontaneous regeneration. The objective of this work was to study the physiological quality of T. fuchsiaefolia seeds, in function of temperature, substrate and accelerated aging, evaluate the emergence and growth of seedlings in different substrates and shading levels. For germination, seed were sowing on substrates: paper roll, with seed upon paper, upon sand, upon coconut fiber, upon HS-Florestal® and upon vermiculite, and six temperatures, 20, 25, 30, 35, 20-30 e 20-35 °C in a experimental design completely randomized, with four replicates of 25 seeds. The seeds were kept in a germination chamber BOD (Biochemical Oxygen Demand) for 35 days. Were analyzed: germination speed index, percentage of germination, mean germination time, percentage of normal seedlings, length of aerial parts and roots, and dry mass of seedlings. The accelerated aging was conducted in a traditional method, and in NaCl solution, in three temperatures: 41, 43 and 45 ºC, and five periods of exposure: 0, 24, 48, 78 and 96 hours. The seeds, after aging, were germinated in rolls of germitest paper, in four replicates of 25 seeds, in BOD chambers at 30 °C. After 35 days, we assessed the percentage, germination speed index, mean time and frequency of germination; root length and aerial part length, dry matter of seedlings and percentage of normal seedlings. For the emergency test, seeds were sowing in tubes of 53 cm³, six substrates were used: sand, subsoil enriched with sewage sludge, coconut fiber, vermiculite, commercial substrate HS-Florestal® and mixture of HS-Florestal® , vermiculite and coconut fiber; and four levels of shading: full sun, one, two or three screens. After 120 days, were evaluated: emergency, emergency speed index, height of seedling, root length, root collar diameter, dry mass of aerial part and root, leaf area, leaf number and contents of chlorophyll and carotenoids. It is recommended to test the germination of T. fuchsiaefolia seeds the substrates upon sand, upon coconut fiber, upon HS-Florestal® and upon vermiculite; and fixed temperatures of 25 and 30 ºC. The substrates paper roll and upon paper, and temperature of 35 ºC are not suitable for the germination test. The aging method with NaCl is not suitable for testing vigor for the species, since the traditional method, at the temperature of 45 ºC and aging period of 96 hours can be used to test the vigor of T. fuchsiaefolia seeds. The seedlings kept under greater shading showed greater height and leaf area, as well higher levels of chlorophyll. The production of T. fuchsiaefolia seedlings can be performed in sand, HSFlorestal® and mixture of HS-Florestal® , vermiculite and coconut fiber in the intermediate shading, using one of two black screens